Post‐Pictet‐Spengler Cyclization (PPSC): A Strategy to Synthesize Polycyclic β‐Carboline‐Derived Natural Products and Biologically Active N‐Heterocycles. Issue 19 (31st August 2020) - Singh, Rahul; Kumar, Sunil; Patil, Madhuri T.; Sun, Chung‐Ming; Salunke, Deepak B.
Abstract: Pictet‐Spengler reaction is a typical condensation reaction of β‐arylethylamine or Tryptamine with an aldehyde or ketone followed by ring closure to generate tetrahydroisoquinoline (THIQ) and Tetrahydro‐β‐carboline (THβC), respectively. Both these key skeletons represent huge range of structurally diverse naturally occurring isoquinoline and indole alkaloids. Nature has synthesized structurally complex Reserpine, Ajmalicine as well as other related alkaloids using various biosynthetic pathways via Pictet‐Spengler reaction followed by post‐Pictet‐Spengler cyclization (PPSC) stratergy. This biosynthetic process is the short and reliable method to access diverse range of polycyclic heterocycles. Over the period of last sixty years, several researchers have synthesized complex alkaloids without highlighting the synthetic utility of the post‐Pictet‐Spengler cyclization strategy. We summarized the synthesis of numerous natural products and related natural product inspired heterocyclic scaffolds which follow the PPSC strategy to demonstrate its usefulness for the construction of diverse compound collection. Abstract :